Etika Mencari Ilmu Dalam Al-Qur’an (Kajian Q.S. Al-Mujadalah Ayat 11) - Rahmatika Budi Astuti; Maryono Maryono; Salis Irvan Fuadi (Pusat Riset dan Inovasi Nasional, 2023)
Knowledge is needed by humans in achieving life, both in this world and in the hereafter. Ethics are good manners or rules in speaking and behaving. In seeking know ledge also requires ethics. In general, the purpose of this study is to find out abuot the ethics of seeking knowledge contained in surah Al-Mujadalah verse 11, to know the ethical concept of seeking knowledge, to know the various ethics of seeking knowledge, and to know the actualization of the ethical concept of seeking knowledge in the current eucation context. In this study the method used was qualitative research and library research, primary data sources and secondary data, using documentary studies and online data searches, and using data analysis and hermenutical analysis.